Konsep Akhlak menurut Ibn Miskawaih - Syafa'atul Jamal (Tasfiyah: Jurnal Pemikiran Islam, 2017)
This article tries to explain the concept of Akhlak based on Ibn Miskawayh prespective, a concept based on the most important aspects in human beings,namelys; the soul (nafs). Simply, Ibn Miskawayh charted that; power that exist in the human soul can be divided into at least three, including an al-nafs-Nāt}iqah, al-nafs al-Sabū’iyyah and alnafs al-Bahīmiyyah. The three powers have their own characteristics and task, which can sometimes outdo each other with each other. However, on the other hand, they also can be balanced and harmonious. Both of these conditions have the same logical consequences in very different ways. First, if these capacities can be harmonized, then it may quite certainly cauising havoc and misery, either for themself or any other creatures. Second, if they can be balanced as well as in its portion, then that person will get the ultimate happiness and will be reflected in the admirable characteristic. Under this concept, Ibn Miskawayh regarded as one of the figures which were quite successfully systematizing the discussion of akhlak. So some figures afterwards are not awkward for adopting several variables.